Performance of tax-benefit systems amid COVID-19 crises in sub-Saharan Africa: A comparative perspective - Jesse Lastunen; Adnan Shahir; Pia Rattenhuber; Kwabena Adu-Ababio; Rodrigo Carvalho Oliveira (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
We examine the distributional effects of the COVID-19 pandemic and associated tax-benefit measures in seven sub-Saharan African countries, focusing on the onset of the crisis. We evaluate impacts on disposable incomes, considering variations across income groups; assess the effectiveness of tax-benefit policies in mitigating income losses; and analyse the influence of these measures on income-based poverty and inequality. We find notable reductions in disposable incomes, concentrated among higher-income households, and moderate increases in headcount poverty rates and poverty gaps. The study highlights the low effectiveness of pre-existing tax-benefit policies, with coverage gaps for the informal sector and a lack of income-dependent means-tested benefits. Discretionary taxbenefit policies in Mozambique and Zambia cushioned the shock for low-income households to a small extent. Conversely, school closures in Ethiopia and Ghana suppressed the provision of school meals, adding strain to households with school-age children.
Keywords: D31; E24; H24; 330; COVID-19; income distribution; poverty; inequality; Africa